Enhancing cognitive and collaborative outcomes in Islamic education: A classroom action research on the STAD method in aqidah akhlak learning - Saidah, Elbina Mamla; Wahyuni, Wahyuni (Asatiza: Jurnal Pendidikan, 2026)
This study examines the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning method in improving students’ learning outcomes in the "Beriman Kepada Malaikat Allah" (Faith in Allah’s Angels) chapter of the Aqidah Akhlak subject at MTs Asy-Syuhada. Employing a Classroom Action Research (CAR) design based on the Kurt Lewin model, the study was conducted in two cycles comprising planning, action, observation, and reflection stages with 26 seventh-grade students of Class VII B during the 2024/2025 academic year. Data were collected through learning outcome tests, observation sheets of student and teacher activities, and field notes, and analyzed using both quantitative and qualitative approaches. The findings reveal a significant improvement in students’ learning outcomes across cycles, with the average score increasing from 72.1 with 65.3% mastery in Cycle I to 80.4 with 88.4% mastery in Cycle II, surpassing the minimum mastery criterion of 75. In addition, students’ engagement and cooperative learning behaviors improved, particularly in the frequency of peer explanation, where students actively explained concepts to their group members, fostering both understanding and collaboration. These results indicate that STAD is effective not only in enhancing cognitive achievement but also in promoting active collaboration through structured peer interaction. Based on the findings, STAD is a promising strategy for text-based or discussion-heavy subjects in Islamic education at the junior secondary level, especially in subjects like Aqidah Akhlak that require active participation and group cooperation.